Implementasi Model Tumpang Sari Kelapa Sawit dan Semangka di Perkebunan Kelapa Sawit Rakyat Bagan Sinembah Rokan Hilir Riau - Aang Kuvaini; Vira Irma Sari; Doly Syahputra (JURNAL CITRA WIDYA EDUKASI, 2022)
Increasing the area of ??oil palm plantations in Indonesia must be accompanied by a plantation land optimization program so as to provide maximum results in maintaining the sustainability of plantation land in the future. One of the optimization of plantation land is intercropping. This study aims to determine the implementation model of oil palm and watermelon intercropping in smallholder oil palm plantations. This research was conducted directly in the field using the Demonstration Plot (Demplot) method of intercropping oil palm and watermelon. In this method, observations include observations of the condition of the land, soil conditions, physical conditions of oil palm plants and the condition of watermelons. In addition, the in-depth interview method was also conducted for farmers to get an explanation of the process of land preparation, planting, maintenance, and harvesting. The results showed that the implementation of the oil palm and watermelon intercropping model was economically very profitable, reaching Rp. 6,488,800/hectare/season. On the environmental aspect, the intercropping method in oil palm plantations has a very good impact on soil conditions in retaining water, maintaining moisture, and preventing soil erosion.